2021
DOI: 10.1021/acs.jpclett.1c00186
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl Ring: A Steric Hindrance or a Source of Different Hydrogen Bonding Patterns in Self-Organizing Systems?

Abstract: A series of five alcohols (3-methyl-2-butanol, 1-cyclopropylethanol, 1-cyclopentylethanol, 1-cyclohexylethanol, and 1-phenylethanol) was used to study the impact of the size of steric hindrance and its aromaticity on self-assembling phenomena in the liquid phase. In this Letter, we have explicitly shown that the phenyl ring exerts a much stronger effect on the self-organization of molecules via the O–H···O scheme than any other type of steric hindrance, leading to a significant decline in the size and concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Nowok et al have shown that a phenyl ring has a much stronger effect on the self-assembling through the OHÁÁÁOH interactions than any other kind of steric hindrance. 15 This effect leads to the reduction in the size and population of the hydrogen-bonded associates. In addition, the phenyl ring is a source of OHÁÁÁp interactions, which compete with the OHÁÁÁOH ones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowok et al have shown that a phenyl ring has a much stronger effect on the self-assembling through the OHÁÁÁOH interactions than any other kind of steric hindrance. 15 This effect leads to the reduction in the size and population of the hydrogen-bonded associates. In addition, the phenyl ring is a source of OHÁÁÁp interactions, which compete with the OHÁÁÁOH ones.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reveal that the OHÁÁÁp interaction is an important factor affecting the assembling process of phenol and its derivatives in aromatic solvents. 8,[11][12][13][14][15][16][17][18][19][20] The strength of the OHÁÁÁp interactions depends on the number, position, and character of the substituents in the aromatic ring of the solute and solvent. IR studies by Saggu et al have shown that the electron withdrawing substituents weaken the OH(D)ÁÁÁp phenol-solvent interactions, while the electron donating groups have an opposite effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Si O N for Bz/GF and PBz/GF that also has Si O B, and Si O C for PR and Si O B for PPR. 23 Finally, the hydrogen bonds (OH O) of Bz and (OH-π) of PBz 41,42 may further positively enhance their resin/GF interfacial adhesion. Bz-a and PBz 10-a in Figure 8 show increased ILSS by 21.1% but decreased ILSS by 28.5%, respectively.…”
Section: Interlaminar Shear Strength Of Compositesmentioning
confidence: 99%
“…8 Hence, an increased cross-linked density of the PBz 10 matrix and increased interfacial adhesion of PBz 10/GF as demonstrated by ILSS test can improve its flexural properties. On top of that, the steric hindrance induced by the dangling phenyl groups 41 in the phenylboronates of PBz 10 may help stabilize the network structure and contribute to an increased flexural properties. 8 In addition, PBz 15/GF also exhibits an increase by 5.2% and 6.4% in flexural strength and modulus compared to Bz/GF despite its deteriorated interfacial adhesion indicated by ILSS test.…”
Section: Interlaminar Shear Strength Of Compositesmentioning
confidence: 99%